Propuesta para la implementación de las prácticas correctas de higiene (pch) en la microempresa agropecuaria “San Vicente” en el Cantón Guano - Herrera Alvarado, Jhonnatan Stalin (2022)
The agricultural microenterprise "San Vicente" is located in the province of Chimborazo in the song Guano Parroquia San Isidro, La Delicia neighborhood. The staff that works in said microenterprise are very aware of the risks that may arise if they do not comply with the Correct Hygiene Practices (PCH) because they could cause contamination in the products made or worse still cause illnesses in the consumers of their products, for this reason reason, the objective of this research work is to carry out a check list on the Correct Hygiene Practices (PCH) in the microenterprise "San Vicente" to know if it complies with these regulations. In this way, as a first point, the microenterprise was visited to be able to dialogue with the manager to explain the activities that will be carried out in the microenterprise, after which the respective check list could be prepared taking into account the articles that were exposed in the regulations. used which is: ARCSA 057-2015, by means of this regulation the check list of Correct Hygiene Practices (PCH) was elaborated, taking from article 4 to article 21, giving us a total of 18 articles as a result. After visiting the company and carrying out the check list of Correct Hygiene Practices (PCH) in the "San Vicente" microenterprise, the data collected was subsequently analyzed and in this way being able to observe what are the shortcomings that the microenterprise is having on the Correct Hygiene Practices (PCH).